2015
DOI: 10.1007/s10265-015-0753-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and mass introductions from limited origins: genetic diversity and structure of Solidago altissima in the native and invaded range

Abstract: Understanding the origins and diversity of invasive species can reveal introduction and invasion pathways, and inform an effective management of invasive species. Tall goldenrod, Solidago altissima, is a herbaceous perennial plant native to North America and it has become a widespread invasive weed in East Asian countries. We used microsatellite and chloroplast DNA markers to obtain information on neutral processes and on genetic diversity in native and invaded populations of S. altissima and to infer how it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 77 publications
1
32
0
Order By: Relevance
“…Sakata et al. () showed that S. altissima populations in southeastern U.S. are most closely related to the predominant genetic lineage in Japan, suggesting that they are the source populations. Corythucha marmorata is one of the major herbivorous insects on S. altissima in its native range of North America (Cappuccino and Root ), and it was introduced to Japan 15 yr ago, and is still expanding its distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Sakata et al. () showed that S. altissima populations in southeastern U.S. are most closely related to the predominant genetic lineage in Japan, suggesting that they are the source populations. Corythucha marmorata is one of the major herbivorous insects on S. altissima in its native range of North America (Cappuccino and Root ), and it was introduced to Japan 15 yr ago, and is still expanding its distribution.…”
Section: Introductionmentioning
confidence: 99%
“…These species both experience frequent herbivory and periodic episodes of drought. These closely related and ecologically similar species are a widely used model system for studies of plant-insect interactions (e.g., Abrahamson and Weis 1997;Heard and Kitts 2012;Williams and Avakian 2015), plant invasions (e.g., Sakata et al 2015;Szymura and Szymura 2016), life history evolution (e.g., Schmid et al 1995;Hafdahl and Craig 2014), and other issues in evolutionary ecology. We examined the impact of drought stress and early-season clipping on different plant structures (both aboveground and belowground) and on patterns of resource allocation among them.…”
Section: Introductionmentioning
confidence: 99%
“…Although this species is thought to have been introduced more or less worldwide (Semple & Cook 2006), its distribution outside of the New World is uncertain. Its presence was confirmed recently in South Africa (Cheek & Semple 2016), China (Chen & Semple 2011) and Japan (Sakata & al. 2015).…”
Section: Resultsmentioning
confidence: 71%